MINIMIZING IMPLANT FAILURES - SAREEN, DR. SAKSHI; SHAH, DR. JAYATI (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Despite significant advances in devices and techniques, placement of dental implants at a correctposition as per the esthetic, biological, and functional perspective still remains a challenge, because thetrajectory of implants is seldom consistent with that of natural teeth due to the bone loss that followsextraction. Computerized‑implant‑dentistry being highly predictable and minimally invasive in naturehas also allowed implant placement in patients with medical comorbidities (e.g. radiation therapy, blooddyscrasias), in patients with complex problems following a significant alteration of the bony anatomy asa result of benign or malignant pathology of the jaws or trauma and in patients with other physical andemotional problems. With significant achievements accomplished in the field of computerizedimplant‑dentistry, attempts are now been made toward complete automation of implant‑dentistry.